2019
DOI: 10.1021/acs.jproteome.9b00313
|View full text |Cite
|
Sign up to set email alerts
|

MHCquant: Automated and Reproducible Data Analysis for Immunopeptidomics

Abstract: Personalized multipeptide vaccines are currently being discussed intensively for tumor immunotherapy. In order to identify epitopesshort, immunogenic peptidessuitable for eliciting a tumor-specific immune response, human leukocyte antigen-presented peptides are isolated by immunoaffinity purification from cancer tissue samples and analyzed by liquid chromatographycoupled tandem mass spectrometry (LC−MS/MS). Here, we present MHCquant, a fully automated, portable computational pipeline able to process LC−MS/MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 76 publications
3
59
2
Order By: Relevance
“…The two somatic variant peptides reported in the original paper but not identified by NeoFlow showed obviously higher absolute RT errors, suggesting the possibility of false positives. Among the four newly identified somatic variant peptides, two have been reported in a recently published reanalysis of the same data set 39 . These results demonstrate the sensitivity and specificity of NeoFlow in analyzing immunopeptidomics data and the value of RT-based validation as an additional filter to reduce false positives.…”
Section: Articlementioning
confidence: 99%
“…The two somatic variant peptides reported in the original paper but not identified by NeoFlow showed obviously higher absolute RT errors, suggesting the possibility of false positives. Among the four newly identified somatic variant peptides, two have been reported in a recently published reanalysis of the same data set 39 . These results demonstrate the sensitivity and specificity of NeoFlow in analyzing immunopeptidomics data and the value of RT-based validation as an additional filter to reduce false positives.…”
Section: Articlementioning
confidence: 99%
“…Database search of LC-MS/MS data from the three time series experiments was performed with MHCquant 1.5.1 as previously described (Bichmann et al, 2019). Identifications were matched between runs (Tyanova et al, 2016) based on retention time alignment and targeted feature extraction (Weisser and Choudhary, 2017) to integrate respective MS1 areas for all time points and technical replicates.…”
Section: Quantitative Time Series Analysismentioning
confidence: 99%
“…Other than the MIAPE initiative (minimal information about immunopeptidomics experiment), there is a need for standardized and version-controlled bioinformatics workflows, especially when considering potential clinical applications. One of the examples of such a workflow is MHCQuant [74], which also shows superior identification capabilities compared to other identification engines, as well as support for label-free quantitation. Remarkably, authors showed the identification and confirmation of previously undetected neoantigens in a publicly available dataset.…”
Section: Detection and Identification Of Immunopeptides With Mass Spementioning
confidence: 99%